Literacy and motivation for the prevention and control of hypertension among female community health volunteers: a qualitative study from Nepal - Dinesh Neupane; Craig S. Mclachlan; Rupesh Gautam; Shiva Raj Mishra; Michael Thorlund; Mette Schlütter; Per Kallestrup (Taylor & Francis Group, 2015)
Background: The prevalence of hypertension is increasing in Nepal. Thus, there is a need for a programme to improve primary healthcare. One possibility is to assign prevention, diagnosis, and treatment of hypertension to female community health volunteers (FCHVs). Objective: To assess literacy and motivation to be involved in a hypertension prevention and control programme in Nepal among FCHVs. Design: Five focus group discussions (FGDs) were conducted with a total of 69 FCHVs in Lekhnath municipality, Kaski district, Nepal. Seven themes were developed on the basis of data collection: 1) knowledge about hypertension; 2) risk factors of hypertension; 3) prevention and control of hypertension; 4) access to treatment for hypertension in the community; 5) learning about blood pressure measurement; 6) ability to raise blood pressure awareness in the community; 7) possible challenges for their future involvement. Data were analysed using the thematic analysis approach. Results: FCHVs have some knowledge about diagnosis, risk factors, and complications of hypertension. General unanimity was observed in the understanding that hypertension and risk factors needed to be addressed. The willingness of FCHVs to contribute to prevention, control, and management was strong, and they were confident that with some basic training they could obtain skills in hypertension management. Conclusions: Despite limited knowledge about hypertension, FCHVs expressed willingness and readiness to be trained in hypertension management. This study supports the possibility of involving FCHVs in prevention and control of hypertension in Nepal.